Amiloride Relaxes Rat Corpus Cavernosum Relaxation In Vitro and Increases Intracavernous Pressure In Vivo. Issue 4 (1st March 2019) - Campos, Rafael; Claudino, Mário A.; de Oliveira, Mariana G.; Franco-Penteado, Carla F.; Del Grossi Ferraz Carvalho, Fernanda; Zaminelli, Tiago; Antunes, Edson; De Nucci, Gilberto
ABSTRACT: Introduction: The antihypertensive effects of thiazide diuretics such as hydrochlorothiazide are commonly associated with erectile dysfunction. The association of hydrochlorothiazide/amiloride is not associated with erectile dysfunction. The hypothesis is that amiloride has beneficial effect in penile erection and, therefore, counterbalances the hydrochlorothiazide-induced disruptive effect. Aim: To investigate the effects of amiloride and its analogues hexamethylamiloride and benzamil on rat isolated corpus cavernosa (CC) and intracavernous pressure (ICP) in anaesthetized rats. Methods: Rat isolated CC were incubated with amiloride, hexamethylamiloride, and benzamil (10 and 100 μmol/L each), followed by phenylephrine, potassium chloride, and electrical field stimulation (EFS). Their effect on the relaxant responses to EFS and sodium nitroprusside were also determined. Oral (30 mg/kg) and intraperitoneal (3 mg/kg) treatments with amiloride were also investigated on nerve-evoked ICP. Main Outcome Measures: In vitro functional studies and in vivo ICP measurement on rat CC were performed. Additionally, phosphodiesterase type V isoform A1 activity and the mRNA expressions of Na + /H + pump, epithelial sodium channel exchangers (ENaC) channels (α-, β- and γ subunits) and Na + /Ca 2+ exchangers were evaluated in CC tissues. Results: Amiloride and its analogues significantly reduced the phenylephrine-, potassium chloride–, and EFS-induced CC contractions, which were not changed by nitro-L-arginine methyl ester (100 μmol/L) or indomethacin (6 μmol/L). In phenylephrine-precontracted CC tissues, amiloride itself caused concentration-dependent relaxation and significantly increased the EFS-induced relaxation. Oral and intraperitoneal treatment with amiloride significantly increased the ICP. Phosphodiesterase type V isoform A1 activity was not affected by amiloride. Na + /H + pump, ENaC, and Na + /Ca 2+ exchanger mRNA expressions were all detected in rat CC tissues. Clinical Implication: Amiloride analogues may have therapeutic potential for erectile dysfunction. Strength & Limitations: The interesting effect of amiloride in penile erection was observed in both in vitro and in vivo methods. The evidence at the moment is restricted to rat CC. Conclusion: Amiloride reduces in vitro CC contractility and enhances erectile function after oral and intraperitoneal administration, possibly via inhibition of ENaC.